2018
DOI: 10.31227/osf.io/pujv7
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Self Compacting Concrete (Scc) Using Seawater as Mixing Water Without Curing

Abstract: The number of problems found in the construction world include the difficulty or lack of fresh water in some areas to be mixed in the concrete, negligence in the maintenance of concrete and working process of concrete mainly on the concrete structures have a complex reinforcement and high concrete building structures. This study aims to find out the compressive strength, splitting tensile strength, absorption, and porosity of Self Compacting Concrete (SCC) using sea water as mixing water and with or without cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
1
1
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 6 publications
2
2
0
Order By: Relevance
“…The results showed that the addition of 10% and 20% bagasse ash caused a slight decrease in the workability of mortar but increased long-term microstructure and compressive strength [6]. As with research by Erniati's et all that the strength of concrete is very significant with porosity and concrete microstructure, where concrete strength and microstructure increase with smaller porosity values [7,8,10].…”
Section: Introductionsupporting
confidence: 51%
See 1 more Smart Citation
“…The results showed that the addition of 10% and 20% bagasse ash caused a slight decrease in the workability of mortar but increased long-term microstructure and compressive strength [6]. As with research by Erniati's et all that the strength of concrete is very significant with porosity and concrete microstructure, where concrete strength and microstructure increase with smaller porosity values [7,8,10].…”
Section: Introductionsupporting
confidence: 51%
“…The compressive strength of concrete is very significant with its porosity and microstructure [7,8]. The higher the concrete compressive strength, the smaller the porosity value [8,10].…”
Section: B Compressive Strengthmentioning
confidence: 99%
“…The results showed that the addition of 10% and 20% bagasse ash caused a slight decrease in the workability of mortar but increased long-term microstructure and compressive strength [6]. As with research by Erniati's et all that the strength of concrete is very significant with porosity and concrete microstructure, where concrete strength and microstructure increase with smaller porosity values [7,8,10].…”
Section: Introductionsupporting
confidence: 51%
“…The compressive strength of concrete is very significant with its porosity and microstructure [7,8]. The higher the concrete compressive strength, the smaller the porosity value [8,10].…”
Section: B Compressive Strengthmentioning
confidence: 99%